Photocatalytic activity of porous multiwalled carbon nanotube-TiO2 composite layers for pollutant degradation - Zouzelka, Radek; Kusumawati, Yuly; Remzova, Monika; Rathousky, Jiri; Pauporté, Thierry (Journal of hazardous materials, 2016)
TiO2 nanoparticles are suitable building blocks nanostructures for the synthesis of porous functional thin films. Here we report the preparation of films using brookite, P25 titania and anatase pristine nanoparticles and of nanocomposite layers combining anatase nanoparticles and multi-walled carbon nanotube (MWCNT) at various concentrations. The structure and phase composition of the layers were characterized by X-ray diffraction and Raman spectroscopy. Their morphology and texture properties were determined by scanning electron microscopy and krypton adsorption experiments, respectively. Additionally to a strong absorption in the UV range, the composites exhibited light absorption in the visible range as well. The photocatalytic performance of the layers was tested in the degradation of aqueous solutions of 4-chlorophenol serving as a model of an eco-persistent pollutant. Besides the determination of the decrease in the concentration of 4-chlorophenol, also the formation of intermediate degradation products, namely hydroquinone and benzoquinone, was followed. The presence of MWCNTs had a beneficial effect on the photocatalytic performance, a marked increase in the photocatalytic degradation rate constant being observed even at very low concentrations of MWCNTs. Compared to a P25 reference layer, the first order rate reaction constant increased by about 100% for the composite films containing MWCNTs at concentrations above 0.6 wt%. The key parameters for the enhancement of the photocatalytic performance are discussed. The presence of carbon nanotubes influences beneficially the degradation of 4-chlorophenol by an attack of the primarily photoproduced hydroxyl radicals onto the 4-chlorophenol molecules. The degradation due to the direct charge transfer is practically not influenced at all.
Keywords: 4-Chlorophenol; Carbon nanotubes; TiO2; Nanocomposite; Photocatalysis